2020
DOI: 10.1111/jomf.12685
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Parental Values in a Period of U.S. Labor Market Change

Abstract: This article examines changes from 1986 to 2016 in the characteristics that parents in the United States most value in their children and differences in those values by parent income and education. Background: As a result of interrelated labor market changes, income-and education-based differences in parents' terminal values that have characterized U.S. families for generations are hypothesized to have converged by income and education during this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…In C3, an inflection on kindness and understanding emerged within the configuration of values centred on relationships. This is consistent with survey evidence that parents are increasingly likely to value compassion (Nomaguchi and Milkie, 2019; Ryan et al, 2020). Ruth [LH314, b.1971; Low SES] recounted being upset when her son was ‘smart’ with another child in public:You know, it was mean and I didn’t like it and I explained to him that people get hurt, some people are different than other people are, some people have thicker skins and other people don’t and you could hurt that child if he doesn’t understand what you are going to do.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…In C3, an inflection on kindness and understanding emerged within the configuration of values centred on relationships. This is consistent with survey evidence that parents are increasingly likely to value compassion (Nomaguchi and Milkie, 2019; Ryan et al, 2020). Ruth [LH314, b.1971; Low SES] recounted being upset when her son was ‘smart’ with another child in public:You know, it was mean and I didn’t like it and I explained to him that people get hurt, some people are different than other people are, some people have thicker skins and other people don’t and you could hurt that child if he doesn’t understand what you are going to do.…”
Section: Methodssupporting
confidence: 87%
“…There is also evidence of variation by gender (Xiao, 2000) and racial and ethnic background (Baker and Barg, 2019). Recent studies show a ‘curvilinear’ pattern of change across birth cohorts in the USA, with younger parents valuing autonomy less than those born at mid-century (Starks and Robinson, 2007), alongside increasing emphasis on ‘hard work’ and ‘caring for others’, and narrowing social class differences (Nomaguchi and Milkie, 2019; Ryan et al, 2020). Alwin and Tufiș (2021) concluded that parental education remains the most important predictor of child-rearing values, mediated by occupational class, with religion having a secondary effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Parents' private contributions of time and money likely facilitate the unequal distribution of educational opportunities both within and across schools; indeed, although parent involvement in the school may be a public good (Murray et al, 2019), more recent scholarship on inequality has characterized the school organizations like the PTA as an example of the "opportunity hoarding" of high-SES parents (Calarco, 2018;Cucchiara & Horvat, 2009;Lareau & Horvat, 1999;Reeves, 2017). Popular explanations for the observed increase in high-income parental investments in the home environment include that the increasing competition for scarce spots in elite universities motivates highincome parents to increase the time they spend at home cultivating their child's skills (Ramey & Ramey, 2010) and, generally, high-income parents perceive greater competition for remunerative careers for their children (Ryan et al, 2020). The same phenomena could explain income-based gaps in how parents spend their time at their child's school.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have identified individual characteristics of low-income parents, such as their knowledge and values, as a mediator linking poverty and less optimal child development (Lareau, 2011;Raz & Beatty, 2018). However, more recent evidence shows that parents' beliefs and ideas about the characteristics and skills their children need to be successful in school have become increasingly similar across all income and education levels (Ryan et al, 2020). Similarly, all parents regardless of SES mostly support "concerted cultivation," which involves time-intensive, child-centered parenting, rather than "natural growth," which involves less intensive, adult-centered parenting (Ishizuka, 2019).…”
Section: Effects Of Poverty On Familiesmentioning
confidence: 99%